INVESTIGATION OF ANTIMICROBIAL ACTIVITY OF SILVER NANO PARTICLE LOADED COTTON FABRICS WHICH MAY PROMOTE WOUND HEALING. - SOURAV GHOSH; ASHUTOSH UPADHAY; ABHISHEK KR.SINGH; ARVIND KUMAR (International Journal of Pharma and Bio Sciences, 2010)
Stable silver nanoparticles were prepared by the chemical process; these particles are incorporated in cotton fabrics. These cotton fabrics with silver nanoparticles are sterile and can be useful in to prevent or to minimize infection with pathogenic bacteria such as Staphylococcus aureus and Escherichia coli. The antimicrobial activity of Ag nanoparticles was investigated against Escherichia coli (MTCC-2940) Gram-negative bacterium, and Staphylococcus aureus (MTCC-74) Gram-positive bacterium. In these tests perform by the agar plates diffusion method were used and Ag nanoparticles loaded cotton fabrics to compare with Ampicillin loaded cotton. As results the growth-inhibitory effects on S. aurous were mild where as the growth-inhibitory effects on E.coli more potent and also perform dose dependent potency test of silver nanoparticles, when doses are increase so antimicrobial activity of Ag particles are increase. The bacteriostatic activity of Ag nanoparticles was evaluated by the help of SEM after 24 h incubation of bacterial strain inoculated cotton fabrics and calculated percent reduction of bacteria. Wound healing is a complex process and has been the subject of intense research for a long time. We therefore hypothesized that silver nanoparticles could improve the healing of burn wounds initially on the basis of the known antimicrobial property of silver.